Keratinocytes, Innate Immunity and Allergic Contact Dermatitis - Opportunities for the Development of In Vitro Assays to Predict the Sensitizing Potential of Chemicals - Veen, Jochem W. van der; Vandebriel, Rob J.; Loveren, Henk van; Ezendam, Janine (IntechOpen, 2011)
None